The International Classification of Functioning, Disability and Health (ICF): elaboration process and debate about the disability question - Mângia, Elisabete Ferreira; Muramoto, Melissa Tieko; Lancman, Selma (Revista de Terapia Ocupacional da Universidade de São Paulo, 2008)
The problem of disability has social and economic relevance to the most countries and dramatic proportions whether considering the appreciation of the existence of 600 millions of disabled people in the world. The World Health Organization (WHO) has systematically alerted the countries about the insufficiency of promoting programs of disabled people and underlies the necessity in comprehend this problem as a social responsibility question, especially concerning the guarantee of rights of people with disabilities. In this context, this paper intend to present the International Classification of Functioning, Disability and Health - ICF - and some related discussions, as: the social construction of disability; the transition process between the ICIDH - International Classification of Impairments, Disabilities and Handcaps - and ICF; its conceptual basis and some theoretical considerations about the instrument. To achieve this, the paper explore especially three articles, whose reading we recommend: "La seconda classificazione internazionale di defcit, disabilitá e handicap dell'pms: confronto e integrazione di modelli di disabilitá", organized by Barbara D'Avanzo (2000), "Models of disablement, universalism and international classification of impairments, disabilities and handcaps", of Bickenbach and others (1999) and "Desmystifying disability: a review of the International Classification of Functioning, Disability and Health", by Rob Imrie.